Low-Glare Freeform-Surfaced Street Light Luminaire Optimization to Meet Enhanced Road Lighting Standards - Lee, Jetter; Le, Lanh-Thanh; Le, Hien-Thanh; Liao, Hsing-Yuan; Huang, Guan-Zhi; Ma, Hsin-Yi; Wen, Chan-Chuan; Fang, Yi Chin; Chen, Chao-Hsien; Chang, Shun-Hsyung; Lee, Hsiao-Yi (International Journal of Optics, 2020)
To enhance driving safety at night, a new freeform-surface street light luminaire was proposed and evaluated in this study that meets the requirements of the International Commission on Illumination (CIE) M3 class standard for road lighting. The luminaire was designed using simulations to optimize the location of the bulb according to the requirements of the standard. The light source IES file was experimentally obtained for the optimized luminaire prototype with a 150 W ceramic metal halide lamp using an imaging goniophotometer. The trial road lighting simulation results computed by the lighting software DIALux indicated that the proposed luminaire provided an average road surface brightness of 1.1 cd/m2 (compared to a minimum requirement of 1.0 cd/m2), a brightness uniformity of 0.41 (compared to a minimum requirement of 0.4), a longitudinal brightness uniformity of 0.64 (compared to a minimum requirement of 0.6), and a glare factor of 7.6% (compared to a maximum limit of 15%). The findings of the image goniophotometer tests were then confirmed by the results of a certified mirror goniophotometer test conducted by the Taiwan Accreditation Foundation (TAF). The results of this study can be used to provide improved street lighting designs to meet enhanced international standards.